Post-Soviet migrants in Germany, transnational public spheres and Russian soft power. Issue 3 (2nd July 2020) - Golova, Tatiana
ABSTRACT: When social networking sites based in authoritarian states expand transnationally, digital media environments create soft power resources for these states. Rather than being an intrusion into national cyber-spaces "from outside", these communication networks are constructed by multiple actors, not all of whom are backed or coordinated by the authoritarian state. Diasporic actors are of special interest here. Using reposts as a direct measure of information flows on the Russian social network VKontakte(VK), this article reconstructs Russian-language networks of influence related to post-Soviet migrants in Germany. It shows that transnational communicative spaces evolve around collective resources related to these migrants by tracing how transnational and multidirectional content flow is organized between the post-Soviet space and Germany. Identifiable political sub-networks are found to be dominated by anti-liberal and anti-Western positions, ideologically and thematically compatible with official Russian state discourses. Right-wing radicals, another target audience of Russian soft power strategies in Europe, are shown to be interconnected with the publics of Russian-speakers in Germany and in the post-Soviet space. Communicative spaces on social networks are thus not purely metaphorical, but underpin the extraterritorial reach of authoritarian regime.